GEOCHEMISTRY OF LARGE RIVER SUSPENDED SEDIMENTS: SILICATE WEATHERING OR RECYCLING TRACER? - Gaillardet J.; Dupré B.; Allègre C.J. (My University, 1999)
This study focuses on the major and trace element composition of suspended sediments transported by the world’s largest rivers. Its main purpose is to answer the following question: is the degree of weathering of modern river-borne particles consistent with the estimated river dissolved loads derived from silicate weathering?In agreement with the well known mobility of elements during weathering of continental rocks, we confirm that river sediments are systematically depleted in Na, K, Ba with respect to the Upper Continental Crust. For each of these mobile elements, a systematics of weathering indexes of river-borne solids is attempted. A global consistency is found between all these indexes. Important variations in weathering intensities exist. A clear dependence of weathering intensities with climate is observed for the rivers draining mostly lowlands. However, no global correlation exists between weathering intensities and climatic or relief parameters because the trend observed for lowlands is obscured by rivers draining orogenic zones. An inverse correlation between weathering intensities and suspended sediment concentrations is observed showing that the regions having the highest rates of physical denudation produce the least weathered sediments. Finally, chemical and physical weathering are compared through the use of a simple steady state model. We show that the weathering intensities of large river suspended sediments can only be reconciled with the (silicate-derived) dissolved load of rivers, by admitting that most of the continental rocks submitted to weathering in large river basins have already suffered previous weathering cycles. A simple graphical method is proposed for calculating the proportion of sedimentary recycling in large river basins. Finally, even if orogenic zones produce weakly weathered sediments, we emphasize the fact that silicate chemical weathering rates (and hence CO2 consumption rates by silicate weathering) are greatly enhanced in mountains simply because the sediment yields in orogenic drainage basins are higher. Hence, the parameters that control chemical weathering rates would be those that control physical denudation rates.